Pengaruh Latihan Sirkuit dan Latihan Interval terhadap Peningkatan Daya Tahan Vo₂ Max Ditinjau Dari Kelincahan Siswa Ekstrakurikuler Cabang Bola Voli Kelas 5 SDN 3 Kalahien - Lesie Lesie; Duwi Kurniato Pambudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to test: (1) the differences in the influence of circuit training and interval training on increasing the VO2 Max endurance of extracurricular volleyball students of grade 5 SDN 3 Kalahien, (2) the differences in the influence of high agility and low agility on increasing the VO2 Max endurance of extracurricular volleyball students of grade 5 SDN 3 Kalahien, and (3) the interaction of training types (circuit and interval) and agility (high and low) on increasing the VO2 Max endurance of extracurricular volleyball students of grade 5 SDN 3 Kalahien This research method is an experiment with a quantitative approach in the form of a 2x2 factorial design. The research sample consisted of 20 students with the criteria of students actively participating in volleyball extracurricular activities, being in good physical condition, and having written permission from their parents/guardians to participate in the intensive training program. The measuring instrumentVO₂ Maxmeasured using a testmultistage fitness test (bleep test) and agility is measured through testsagility T-test And shuttle run. The data analysis technique used was two-way ANOVA at a significance level of α = 0.05. The results of the study are (1) there is a significant difference in the influence of circuit training and interval training on increasing the VO2 Max endurance of extracurricular volleyball students of class 5 SDN 3 Kalahien with a significance value of p of 0.020 < 0.05, (2) there is a significant difference in the influence between high agility and low agility on increasing the VO2 Max endurance of extracurricular volleyball students of class 5 SDN 3 Kalahien with a significance value of p of 0.001 < 0.05, (3) there is an interaction between the type of training (circuit and interval) and agility (high and low) on increasing the VO2 Max endurance of extracurricular volleyball students of class 5 SDN 3 Kalahien with a significance value of p of 0.004 < 0.05. The research suggestion is for volleyball sports teachers to choose training methods that are appropriate to the characteristics of student agility.. Keywords: Agility, Endurance VO2 Max, Circuit Training, Interval Training cara keseluruhan.